System requirements analysis for JAXA's contribution to Comet Interceptor mission: autonomous navigation, guidance and attitude control for a hyperbolic comet fly-by - Machuca, Pablo; Ozaki, Naoya; Sánchez, Joan-Pau; Felicetti, Leonard; Funase, Ryu (IAC, 2020)
Comet Interceptor, to be launched in 2028, is a recently-selected ESA/JAXA mission aimed to perform the first fly-by of a pristine long-period comet. As part of the mission’s Phases A/B (feasibility analysis and preliminary design), this work preliminarily analyzes the attitude performance of JAXA’s contribution to the mission, SC B1: one of the two small-spacecraft piggybacked along with ESA’s main spacecraft. This study primarily focuses on the characterization of the dust environment, modelization of dust particle impacts, and analysis of attitude performance through the dust environment. Monte Carlo simulations are implemented to assess the performance of the attitude control system within a highly-active dust environment, for various fly-by altitudes and a worst-case 70-km/s fly-by speed. Results evidence the need for a wide-angle camera, and conclude that image acquisition shall tolerate angular velocities of several degrees per second. Solutions for improved attitude performance are also evaluated (i.e., upgrading of reaction wheels and angular momentum pre-loading), and a larger reaction wheels aligned with the camera line of sight is shown to provide largest performance improvements. Such strategies, nevertheless, still result in pointing errors and angular velocities that are only compatible with a short-exposure, wide-angle science camera
Keywords: system requirements; attitude control; comet fly-by; Comet Interceptor